491 Have we improved uterine serous carcinomas management the last two decades? A single center experience. (4th December 2020) - Liontos, Michail; Svarna, Anna; Zakopoulou, Roubini; Zagouri, Flora; Theofanakis, Charalampos; Thomakos, Nikolaos; Haidopoulos, Dimitrios; Rodolakis, Alexandros; Sotiropoulou, Maria; Dimopoulos, Meletios-Athanasios; Skafida, Efi; Kaparelou, Maria; et al.
Abstract : Introduction/Background: Uterine Serous Carcinomas (USC) account for ten percent of endometrial cancers. Management of the disease is challenging due to its aggressiveness. Despite numerous clinical trials and advances in the molecular pathology of the disease it remains the most lethal uterine carcinoma. We undertook this study to determine changes in the management of the disease and the survival of our patients the last two decades. Methodology: Medical records of women with USC treated at Alexandra Hospital from 2000 to 2018 were retrospectively identified. Clinicopathological data, treatment and survival data were analyzed. Kaplan-Meier Survival curves were generated using Strata SE 15.1; survival differences were estimated using the long-rank test. Results: 121 patients with USC and complete clinical data were identified. Median age was 66.9 years. Pure serous carcinomas were diagnosed in 66 patients, while the remaining had mixed histologies. At diagnosis, 33 patients (28.0%) had stage Ia disease, but also 28 patients had stage IV disease (23.7%). 115 patients were treated with surgery including lymphadenectomy in 63 cases (55.8%) and omentectomy in 83 cases (73.5%). 64 patients (52.9%) were treated from 1999 to 2009. There was no statistical difference in the stage distribution, omission of lymphadenectomy or omentectomy and type of adjuvant treatment among patients treated prior or after 2010. Also, for patients with stage I-III disease, eligible for adjuvant treatment, both disease free survival and overall survival (OS) per stage did not differ significantly between the two decades. Finally, in patients with de novo stage IV disease there was no improvement in either first line Progression Free Survival or OS between the two decades (mPFS 1st vs 2nd decade: 8.6 vs 5.9 months 95% CI [1.5–15.7].[3.4–8.5] and mOS 18.4 vs 11.6 months 95% CI [1.7–34.9].[0.0–25.1]. Conclusion: Despite recent clinical trials, surgical and medical management of USCs had not changed significantly the last two decades in everyday clinical practice. This is reflected in the survival of the patients. Disclosures: Authors have no conflict of interest.